Characteristics contributing to the success of a sports coach - Frost, J. L. (The Sport Journal, 2009)
Identifying particular characteristics (qualities and abilities) of successful sports coaches could offer other coaches help in improving their performance. Toward this end, 15 high school coaches completed a survey on 17 possible such characteristics, ranking 5 of them above the rest (= 90th percentile): quality of practice, communicating with athletes, motivating athletes, developing athletes` sports skills, and possessing knowledge of the sport. Coaches seeking to enhance their success might focus on these characteristics.